Institutionalizing collaborative partnerships in inclusive early childhood education: structured parent-school collaboration practices - R.Rety Riesmawati; Nur; Muhtarom (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2025)
This qualitative case study examined: What mechanisms enable parent-school partnerships to transcend episodic initiatives and become embedded institutional practices in inclusive PAUD contexts? Data were systematically collected through semi-structured interviews with nine key informants, participant observations of 35 instances, and document analysis over five months. The study's most distinctive contribution documents the institutionalization of parent-school partnerships through eight systematically designed collaborative programs formalized in a comprehensive Parent Guidebook: KINASIH (parent peer learning community), Guest Teacher (parent expertise leveraging), Passion Club (parent skill-sharing), Meja Peradaban (cultural literacy), Market Day (entrepreneurship education), Anjangsana (home visits), monthly Parent Meetings (structured dialogue), and Home Visits (individualized family engagement). Analysis revealed five interconnected dimensions of collaborative leadership operating synergistically: shared vision understood across all stakeholder levels; structured communication mechanisms through multiple channels; democratic participatory decision-making; continuous professional development embedded in daily practice; and adaptive flexibility maintaining philosophical consistency. Findings demonstrate effective partnership institutionalization requires: formalizing programs in accessible documentation; establishing systematic multi-channel communication; embedding professional development in daily reflective forums; involving stakeholders democratically in vision formulation; and building programmatic flexibility while maintaining philosophical consistency.